A Systematic Review Comparing The Use Of Double-Row Versus Triple-Row Staples In Colorectal Surgery - Dwi, Nova; Fatmawati (International Medical Journal Corp. Ltd, 2024)
Background: The choice of surgical staplers, such as double-row staples and Tri-Staple, significantly impacts the success of anastomoses. The Tri-Staple technology, developed by Medtronic, improves on the drawbacks of double-row staples, allowing surgeons to use staplers over a wider range of tissue thickness. Methods: PRISMA 2020 guidelines were adhered to in this study in order to guarantee accuracy and consistency in research findings. It featured articles contrasting adult patients undergoing colorectal surgery using double-row and triple-row staple technologies. Result: The majority of procedures used oral antibiotics prior to surgery and were minimally invasive. The risk of anastomotic leak was greatly decreased by triple-row staple technology. Mean operative time, LOS, and mortality data were similar between the two groups. Conclusion: Tri-Staple technology provides better advantages in terms of tissue compression and perfusion. It reduces anastomotic leak risk by 46%, while double-row technology offers a 46% reduction. Tri-staple technology increases staple line perfusion, bursting pressure, and the amount of force needed to take out the stapler.